The Archaeology of Medieval Europe - Crabtree, Pam J. (History compass, 2009)
Modern medieval archaeology developed in the aftermath of World War II. It began as a hybrid discipline, since archaeologists working in the later Middle Ages were often trained in history and architectural history, while those working in the early medieval period were often trained as prehistorians. A major challenge for medieval archaeologists is the integration of material remains (artifacts and features) and historical evidence. Archaeology is not just a handmaiden to history; critical interpretation of both material remains and written texts can shed new light on the so-called Dark Ages. After reviewing the development of modern medieval archaeology, this article examines a number of contemporary issues in the field including the study of urban development, medieval landscapes and settlement patterns, ethnic origins, and gender.